Analisis Perencanaan Bisnis dalam Pengembangan Unit Usaha Pendidikan Berbasis Edutech - Hendi Kurniyawan; Abdullah (INNOVASI : JURNAL INOVASI PENDIDIKAN, 2025)
Digital transformation has driven the development of education technology (Edutech) not only as a learning tool but also as a strategic business unit in the educational environment. However, the sustainability of Edutech-based educational business units is largely determined by the quality of the business planning implemented. This study aims to analyze business planning in the development of Edutech-based educational business units and examine its implications for business sustainability. This study uses a descriptive qualitative approach with data collection techniques through in-depth interviews, observations, and documentation studies. Research informants were selected purposively from managers and stakeholders of Edutech-based educational business units. Data analysis was conducted thematically through the stages of data reduction, data presentation, and conclusion drawing, and was strengthened by triangulation of sources and methods. The results of the study indicate that systematic business planning has significant implications for the sustainability of Edutech business units in three main dimensions: economic, social, and operational. Business planning contributes to financial stability, efficient resource management, strengthened relationships with stakeholders, and increased adaptability and innovation of digital services. These findings also confirm that business planning functions as a strategic mechanism that integrates educational objectives, business strategies, and technology utilization. Based on a synthesis of empirical findings and a theoretical framework, this study formulates an ideal business planning model for an Edutech-based educational business unit that is integrative, adaptive, and oriented toward sustainable innovation. This research is expected to provide theoretical contributions to the development of educational management and Edutech studies, as well as practical recommendations for educational business unit managers in the digital era.